Examining potential health gains arising from reduced risk consumption in South Africa via the PRIME model - Steven F. Koch (Springer, 2024)
Abstract Objectives Non-communicable diseases (NCDs) account for over 30% of disability-adjusted life years in South Africa. In this research, we offer an estimate of the potential reduction in NCD incidence that would arise from an improvement in diet, combined with a reduction in both tobacco and alcohol consumption. Methods We apply the PRIME model, which simulates the effect of risk reduction on NCD incidence. The model inputs baseline data related to the population, risky consumption behaviour and NCD incidence. The model allows for counterfactual scenarios altering the risky consumption behaviour to yield revised NCD incidence. Results We find that reducing salt, tobacco and alcohol, along with improved fruit, vegetable and fiber consumption would yield a 10% reduction in NCDs from the 2018 baseline. NCD incidence reductions arise primarily from ischemic heart disease (49%), cerebrovascular diseases (33%) and bronchus and lung disease (11%). Conclusion South Africa's NCD incidence is high because of relatively poor behavioural choices, despite plans and policies aimed at changing this. South Africa should increase their efforts to reach NCD goals. If the government is able to reduce harmful behaviour, with respect to a number of the underlying consumption choices, NCD incidence is expected to fall precipitously.